Strategi Brand Awareness Pasar Modern Intermoda BSD City - Salsabila Aulia Putri; Syahra Amanda Heridian; Irma Juliani Fajrin; Ni Gusti Ayu Ketut Kurniasari (UHN IGB Sugriwa Denpasar, 2023)
Intermoda Modern Market in BSD City is a modern market with a new concept. The thing that distinguishes this modern market from other modern markets is that it provides the concept of a modern market which is not only a place for shopping but also a place for family recreation. Intermoda Modern Market in BSD City combines various concepts, including shopping, culinary tours, children's play areas (playground), and gathering places. Brand Awareness (brand awareness) is the ability of consumers to recognize brands in different situations, this can be done with brand recognition and recall of a particular brand. This study used a qualitative descriptive method with research techniques focused on focus group discussions (FGD). FGDs are conducted by involving managers, consumers and traders. This research resulted in three things, namely facilities, services and promotion, where these three things are important components in forming a brand awareness strategy for the Intermoda Modern Market in BSD City.